Leading the Maricopa Millions OER Project. Issue 7 (2nd July 2016) - Raneri, April; Young, Lisa
ABSTRACT: With a reduced number of students purchasing required and necessary textbooks, higher education leaders must look to new opportunities to increase student success. While open educational resources have addressed this issue, they have not received widespread support from faculty, staff, and administrators. The Maricopa Millions OER Project: Scaling Use of ExtraOERdinary Materials from Maricopa Community Colleges was evaluated for its ability to create and implement a low- to no-cost textbook initiative that aims to lower course material cost for students and increase access to resources, while maintaining quality curriculum and instruction and promoting faculty and staff buy-in. Several models, including John Kotter's eight-step Process for Leading Change, Bridges's Transition Model, the Planned Change Model, and Adoption of Innovations, were found to be utilized throughout the process of development and implementation of the project.